THE ROLE of GENERAL PRACTITIONER in POST-TRAUMATIC STRESS DISORDER PATIENT - Nuralitha, Amira (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Post-traumatic stress disorder (PTSD) is a mental illness whose criteria are listed in DSM-5 and ICD 11 marked by an inability to recover after experiencing or watching a horrific event that lasts more than 1 month. PTSD should be considered in any patient who has experienced a significant tumultuous occasion. Methods – The author makes this article based on several kinds of literature that discuss PTSD, the role of GP in PTSD patients, psychological first aid, and psychological, and pharmacological treatment for PTSD patients. The literature used is limited from 2009 to 2021. Results – Approximately 3% of the adult population suffers from PTSD. Often the first point of contact, General Practitioners are positioned to assist patients who have contemporarily experienced a traumatic life event and who are at risk for developing PTSD. Discuss –Post-traumatic stress disorder (PTSD) is a mental illness whose criteria are listed in DSM V and ICD 11 marked by an inability to recover after experiencing or watching a horrific event that lasts more than 1 month that can be treatable. As primary healthcare providers, general practitioners are the first healthcare practitioners accessible to individuals who have experienced a horrifying episode. Conclusion – General practitioners take an important part in recognizing people with PTSD and giving psychological first aid, managing their care with psychological or pharmacological treatment, and referring them for specialized care when needed.  Keywords: post-traumatic stress disorder, general practitioner, psychological.